Evaluation of Possible Effects of Hyoscine in Xylazine-Induced Fetal Death in Pregnant Rats - Mona Zohani-Ghayeni; Siamak Kazemi-Darabadi; Abolfazl Hajibemani; Ghasem Akbari (Iranian Journal of Veterinary Surgery, 2023)
Although xylazine is widely used in domestic animals as a sedative, analgesic, and muscle relaxant, its side effects on the uterus prevent its utilization in pregnant animals or in embryo transfer. Although the effects of xylazine on increasing uterine contractions have been confirmed, no reliable report of fetal death due to xylazine administration has been published. Hyoscine is an anticholinergic medication that has antimuscarinic and antispasmodic effects in the uterine tissue of pregnant cattle during in vitro studies, therefore, we investigated if administration of xylazine in the last third of pregnancy could increase fetal death and if hyoscine could prevent its adverse effects. Twenty adult female rats, after mating with four adult male rats and confirming pregnancy, were randomly divided into two equal control and treatment groups. On the 18th day of pregnancy, the number of fetuses per rat was determined using ultrasonography. Rats in the treatment group received hyoscine (1 mg/kg, intraperitoneally) for 3 days. Subsequently, all rats were administered xylazine (10 mg/kg, intraperitoneally) for 3 days. On the 21st day of pregnancy, the number of living and dead fetuses was counted after laparotomy. Also, the weight and dimensions of the fetuses were measured. The results showed that although more fetuses lost their lives in the treatment group compared to the control group, the statistical difference in the percentage of fetal mortality in the two groups was not significant (p  0.05). In addition, the comparison of the mean weight, body length, and body width of living and dead fetuses in both groups showed that there was no statistically significant difference between these groups (p  0.05). It could be concluded that maternal xylazine intake in rats could cause about 18-25% of fetal mortality. However, the use of hyoscine to prevent fetal death induced by xylazine is not recommended.